The Role of Islamic Religious Education Teachers in Instilling Religious Character in Students at the Rammatul Asri Islamic Boarding School Junior High School, Enrekang Regency - Muh. Fikram; Wardah Hanafie Das; Muhammad Fadli (Universitas Muhammadiyah Palu, 2026)
Education is the main foundation in the formation of quality human resources, not only intellectually, but also morally and spiritually. This study uses a qualitative research method that aims to explore and understand in depth the phenomenon of the role of Islamic Religious Education (PAI) teachers in instilling religious character in students at Islamic Boarding Schools. This study shows that Islamic Religious Education teachers at SMPS Pondok Pesantren Rahmatul Asri play a strategic role as educators, guides, and role models for students. The instillation of religious character is carried out through various methods, including PAI teachers who lead by example, habituate worship, advice (mau'izhah hasanah), the provision of educational punishment, and the involvement of students in religious activities. Students show positive changes in their worship habits, ability to maintain morals, and a sense of responsibility towards themselves and their environment. This success is inseparable from the collaborative role of PAI teachers, the support of the principal, the head of the Islamic boarding school, and the active participation of students.